Malala’s Life as a Stage for Identity and Change - Rajbanshi, Badri Narayan (Mindscape: A Journal of English & Cultural Studies, 2024)
This paper explores Malala Yousafzai’s autobiography, I Am Malala, through the lens of identity performance and transformation. It argues that Malala’s life, as narrated in her memoir, functions as a stage where multiple identities are enacted and transformed over time. Drawing upon theories from performance studies, particularly Judith Butler’s concept of performativity and Richard Schechner’s theory of restored behavior, the paper analyzes how Malala performs her gender, cultural, and activist identities in response to social and political challenges. The analysis also considers how trauma and global recognition contribute to her identity change and the ways in which she reshapes the narrative of Muslim girlhood. Ultimately, this paper shows how Malala’s life is not just a story of survival but a powerful example of identity as a dynamic and performative process.